Effectiveness of Respiratory Muscle Training in Pompe Disease: A Systematic Review and Meta-Analysis - Mu-Yun Lin; Szu-Han Chen; Jen-Ting Lee; Po-Cheng Hsu (MDPI AG, 2024)
Background: Pompe disease is a rare metabolic myopathy caused by the lack or deficiency of the lysosomal acid alpha-glucosidase, resulting in skeletal muscle weakness and cardiomyopathy. The disease varies by onset age and genetic mutations and is categorized into infantile-onset and late-onset Pompe disease. Respiratory muscle weakness may persist regardless enzyme replacement therapy. This systemic review and meta-analysis aim to assess the effect of respiratory muscle training (RMT) on respiratory muscle strength, functional endurance, and pulmonary function in patient with Pompe disease. Methods: PubMed, EMBASE, and Cochrane databases were searched up until Aug 2024. Studies examining the therapeutic effects of RMT in patients with Pompe disease were included. Outcome measures included the change in maximal inspiratory pressure (MIP), maximal expiratory pressure (MEP), six-minute walking test (6MWT), pulmonary function before after RMT, quality of life and adverse events. Results: The meta-analysis consisted of 5 single-arm studies, including 31 patients in total. Regarding inspiratory muscle strength, RMT has significantly improving MIP (8.71 cmH2O; 95% CI, 6.23-11.19, p < 0.001) and MEP (12.15 cmH2O; 95% CI, 10.55-13.74, p < 0.001) in both types of Pompe disease. However, no significant change regarding 6MWT. No serious adverse events were reported. Conclusions: Our meta-analysis revealed that RMT may increase inspiratory muscle and expiratory muscle strength, but may not have an effect on 6MWT in patients with Pompe disease. RMT has potential to be integrated into the cardioplulmonary rehabilitation for patients with Pompe disease. Further large randomized controlled trials are needed to verify the efficacy and safety of RMT in patients with Pompe disease.